A single gene in Fusarium oxysporum limits host range. (4th November 2020) - Li, Jiming; Fokkens, Like; Rep, Martijn
Abstract: Fusarium oxysoporum f. sp. radicis‐cucumerinum (Forc) is able to cause disease in cucumber, melon, and watermelon, while F. oxysporum f. sp. melonis (Fom) can only infect melon plants. Earlier research showed that mobile chromosomes in Forc and Fom determine the difference in host range between Forc and Fom. By closely comparing these pathogenicity chromosomes combined with RNA‐sequencing data, we selected 11 candidate genes that we tested for involvement in the difference in host range between Forc and Fom. One of these candidates is a putative effector gene on the Fom pathogenicity chromosome that has nonidentical homologs on the Forc pathogenicity chromosome. Four independent Forc transformants with this gene from Fom showed strongly reduced or no pathogenicity towards cucumber, while retaining pathogenicity towards melon and watermelon. This suggests that the protein encoded by this gene is recognized by an immune receptor in cucumber plants. This is the first time that a single gene has been demonstrated to determine a difference in host specificity between formae speciales of F. oxysporum . Abstract : A single putative effector gene from melon‐infecting Fusarium oxysporum f. sp. melonis is able to turn cucumber‐, melon‐ and watermelon‐infecting F. oxysoporum f. sp. radicis‐cucumerinum nonpathogenic towards cucumber plants.